Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/s2542-5196(21)00263-1
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of exposure to e-waste: an updated systematic review

Abstract: Summary Electronic waste (e-waste) contains numerous chemicals harmful to human and ecological health. To update a 2013 review assessing adverse human health consequences of exposure to e-waste, we systematically reviewed studies reporting effects on humans related to e-waste exposure. We searched EMBASE, PsycNET, Web of Science, CINAHL, and PubMed for articles published between Dec 18, 2012, and Jan 28, 2020, restricting our search to publications in English. Of the 5645 records identified, we incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 107 publications
1
25
0
Order By: Relevance
“…The total effects of pollution on health would undoubtedly be larger if more comprehensive health data could be generated, especially if all pathways for chemicals in the environment were identified and analysed. 5 The GBD 2019 data show that the effect of pollution on disease and disability varies by sex. Men are more likely to die from exposure to ambient air pollution, lead pollution, and occupational pollutants than women.…”
Section: Pollution-related Deathmentioning
confidence: 99%
“…The total effects of pollution on health would undoubtedly be larger if more comprehensive health data could be generated, especially if all pathways for chemicals in the environment were identified and analysed. 5 The GBD 2019 data show that the effect of pollution on disease and disability varies by sex. Men are more likely to die from exposure to ambient air pollution, lead pollution, and occupational pollutants than women.…”
Section: Pollution-related Deathmentioning
confidence: 99%
“…A data extraction form was adapted from Parvez et al (2021) [ 24 ] to collect the relevant information from each included study. We developed a standardized protocol to include the following study characteristics: name of author and year of publication, study design, location study was conducted, sample size, type of pollutant(s) assessed, health outcomes measured, and effect sizes of the association between the exposures and health outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…E-waste exposure has been reported to be associated with adverse health outcomes such as DNA damage [ 19 ], decreased lung function [ 20 , 21 ], change in thyroid function, adverse neonatal outcomes, changes in temperament and behaviour [ 1 ], and a myriad of chronic disease risks, including cancer [ 22 , 23 ]. A recent systematic review update on the health consequences of e-waste exposure by Parvez et al (2021) [ 24 ] found 70 studies that concluded that “the existence of various toxic chemicals in e-waste recycling areas impose plausible adverse health outcomes”. Almost all these studies ( n = 66/70) were conducted in China, while only one study conducted by Burns et al (2016) [ 25 ] was focused on Africa (Ghana).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary outcomes include the impacts of heavy metals on body function. In our recent published systematic review [ 34 ], we have identified the reported health consequences of e-waste exposure ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%